2019
DOI: 10.1097/iae.0000000000001980
|View full text |Cite
|
Sign up to set email alerts
|

Macular Atrophy Findings by Optical Coherence Tomography Angiography Compared With Fundus Autofluorescence in Treated Exudative Age-Related Macular Degeneration

Abstract: The MA and CC nonperfusion areas markedly overlapped. The area of CC nonperfusion correlated with the MA area. Choroidal ischemia might be involved in the pathogenesis of MA in treated age-related macular degeneration.This is an open access article distributed under the Creative Commons Attribution License 4.0 (CCBY), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The commercially available OCTA systems include SSADA algorithm based AngioVue system (Optovue, Inc., Fremont, CA, USA), 89 OMAG algorithm based AngioPlex system (Carl Zeiss Meditec Inc., Dublin, CA, USA) spectral domain OCTA,202 amplitude decorrelation algorithm based sweptsource optical coherence tomography Angio (Topcon Corp., Japan),231 and OCTA ratio analysis algorithm based Heidelberg Spectralis OCTA (Heidelberg, Germany) 227. OCTA has potential applications in evaluation and management of various eye diseases like age related macular degeneration,201,237,32 diabetic retinopathy,136,92 diabetic macular edema, 40 choroidal neovascularization, 39 retinal vascular occlusion,…”
mentioning
confidence: 99%
“…The commercially available OCTA systems include SSADA algorithm based AngioVue system (Optovue, Inc., Fremont, CA, USA), 89 OMAG algorithm based AngioPlex system (Carl Zeiss Meditec Inc., Dublin, CA, USA) spectral domain OCTA,202 amplitude decorrelation algorithm based sweptsource optical coherence tomography Angio (Topcon Corp., Japan),231 and OCTA ratio analysis algorithm based Heidelberg Spectralis OCTA (Heidelberg, Germany) 227. OCTA has potential applications in evaluation and management of various eye diseases like age related macular degeneration,201,237,32 diabetic retinopathy,136,92 diabetic macular edema, 40 choroidal neovascularization, 39 retinal vascular occlusion,…”
mentioning
confidence: 99%
“…OCT angiography studies have shown choriocapillaris nonperfusion in both GA and macular atrophy. 25, 26 Nonperfusion is more extensive in macular atrophy compared to GA and extends outside the areas of visible atrophy. The addition of the neovascular process to an already damaged RPE and choroidal vasculature could potentially result in worsening of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, the development of neovascular AMD in eyes with GA is a known entity with incidence in the Beaver Dam Eye study at 10.9% and the Blue Mountain Eye Study at 22% over 5 years. 26, 27 Recent advanced imaging studies using OCT angiography have, in fact, shown unsuspected quiescent neovascularization adjacent to areas of GA. 28, 29 Conversely, the development of GA in eyes with neovascular AMD has been rarely studied before anti-VEGF therapy as we were unable to identify atrophy in the presence of fibrosis, pigment and photocoagulation scars. It may be that the development of atrophy is the final common pathway of AMD, with the neovascular process intercepting the pathway in some eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Takasago et al found that the choriocapillaris (CC) nonperfusion area and MA area were significantly correlated as these areas markedly overlapped. They concluded that choroidal ischaemia might be thus involved in the pathogenesis of MA in treated nAMD, and that CC nonperfusion after anti-VEGF might be associated with the development of MA [72]. Mastropasqua et al reported intravitreal administration of aflibercept to be associated with a significant reduction of flow in both native retinal and choroidal vasculature in patients' treated eyes [73].…”
Section: Subfoveal Choroidal Thicknessmentioning
confidence: 99%